Equity across Generations and Uncertainty within a Generation: A Welfare Analysis of the National Pension System - Kyooho Kwon (KDI Journal of Economic Policy, 2019)
This paper utilizes a life-cycle overlapping-generations model to quantify the welfare effects of plans to postpone the depletion of the National Pension Fund. In order for the model to incorporate the rapidly changing demographic structure of Korea fully, we build and calibrate a model in transition directly. The model is considered suitable for analyzing the effects of demographic changes on the Korean economy and the effects of plans to change the National Pension System. According to a simulation of the model, to postpone the depletion of the National Pension Fund for 30 years, the premium rate must be increased to 18.3% from the current rate of 9%. By postponing the depletion of the fund reserve, young and future generations gain significantly at the expense of the older generations. The simulation results should be, however, interpreted as meaning that the current system is unjustifiably partial to the older generations. Moreover, given the current premium rate, it is desirable to strengthen the incomeredistribution function of the National Pension System.
Keywords: C68; E21; J11; 330; Heterogeneous Agent Models; Population Aging; National Pension System; Pension Reform